Film/substrate interactions and superconducting properties of Tl(Ba1-xSrx)(2)Ca2Cu3Oy thin films on (001) SrTiO3 and SrTiO3-buffered (001) MgO substrates - Bramley, A; Grovenor, C; Goringe, M; O'Connor, J; Jenkins, A; Dew-Hughes, D; Reschauer, N; Wagner, H; Brozio, W; Spreitzer, U; Renk, K (1998)
We have developed a process for the fabrication of (001) oriented SrTiO3 buffer layers onto (001) MgO substrates by rf magnetron sputtering followed by a post-deposition heat treatment in air. Precursor films with Tl:Ba:Ca:Cu ratio 2:2:2:3 were deposited by dc magnetron sputtering onto both these buffered substrates and directly onto (001) SrTiO3 single-crystal substrates, and thalliated at elevated temperatures. Because of_ Sr diffusion from the substrate/buffer layer, and its subsequent substitution for Ba in the superconducting film, the single Tl-O layer phase Tl(Ba1-xSrx)2Ca2Cu3O y was stabilized. Diffusion of Ba and Ca in the opposite direction led to the formation of a Ba-Ca-Ti-O compound at the interface. The Tl(Ba1-xSrx)2Ca2Cu3O y films typically have superconducting transition temperatures (Tc's) > 103 K and critical current densities (Jc's) > 2.9 × 105 A cm-2 at 77 K. Rs values measured on these films and scaled to 10 GHz were 3.0 mΩ at 80 K and <200 μΩ at 50 K for the film grown on SrTiO3 buffered MgO, and 2.0 mΩ and 1.0 mΩ at 50 K for the film grown directly onto the (001) SrTiO3 substrate. Films fabricated on (001) SrTiO3 using an in situ deposition technique with a substrate temperature around 100°C lower than the ex situ thalliation temperature showed no evidence of an interfacial reaction layer.